Surf's up [videorecording (DVD)] (Sony Pictures Home Entertainment, 2007)
Cody, a Rockhopper penguin, journeys from his home in Shiverpool, Antarctica, to take part in the Big Z Memorial Surf-Off on beautiful Pen Gu Island. During his adventure he meets many new friends, including surf nut Chicken Joe and high-spirited lifeguard Lani. Cody believes that winning is everything until he meets Geek, an old, washed-up pro surfer, who may just show Cody that a true winner isn't always the one who comes in first.